2019
DOI: 10.1002/er.4891
|View full text |Cite
|
Sign up to set email alerts
|

An updated short chemical‐kinetic nitrogen mechanism for carbon‐free combustion applications

Abstract: Chemical-kinetic combustion mechanisms for hydrogen-oxygen-nitrogen systems, motivated originally by concerns about NO x emissions during hydrogen burning, have recently acquired renewed interest as a result of the possibility of employing ammonia-hydrogen mixtures in gas turbines and reciprocating engines as drop-in fuel to replace the use of natural gas. Specifically, this is of relevance to the implementation of engineering approaches for economical power generation with carbon sequestration or to large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…To validate model performances for neat ammonia ignition delay times under rapid compression machine conditions, two sets of IDT measurements were adopted: the temperature-dependent IDT measurements from He et al 71 for equivalence ratios of 0.5, 1.0, and 1.5 at pressures of 4.0 and 6.0 MPa (as shown in Figure 9) and the pressuredependent measurement from Dai et al 76 for the equivalence ratio from 0.5 to 3.0 at 1140 and 1200 K (as shown in Figure 10). As seen in both figures, the mechanisms Jiang-2019, 138 Li-2019, 137 and Mei-2019 91 underestimate the ignition delay time with a factor of 1.5−4 for most conditions, except the case at φ = 3 and T c = 1200 K, where they underestimate the IDT with a factor larger than 5. Dai et al 76 found that Jiang-2019 predicted well the ignition delay times of a lean NH 3 mixture with 70% argon dilution but failed to reproduce the IDTs at other conditions satisfactorily.…”
Section: Combustionmentioning
confidence: 63%
See 2 more Smart Citations
“…To validate model performances for neat ammonia ignition delay times under rapid compression machine conditions, two sets of IDT measurements were adopted: the temperature-dependent IDT measurements from He et al 71 for equivalence ratios of 0.5, 1.0, and 1.5 at pressures of 4.0 and 6.0 MPa (as shown in Figure 9) and the pressuredependent measurement from Dai et al 76 for the equivalence ratio from 0.5 to 3.0 at 1140 and 1200 K (as shown in Figure 10). As seen in both figures, the mechanisms Jiang-2019, 138 Li-2019, 137 and Mei-2019 91 underestimate the ignition delay time with a factor of 1.5−4 for most conditions, except the case at φ = 3 and T c = 1200 K, where they underestimate the IDT with a factor larger than 5. Dai et al 76 found that Jiang-2019 predicted well the ignition delay times of a lean NH 3 mixture with 70% argon dilution but failed to reproduce the IDTs at other conditions satisfactorily.…”
Section: Combustionmentioning
confidence: 63%
“…By updating several reaction rate coefficients of Li-2019, its performance for fuel-rich mixtures was further improved. 67 Since Jiang-2019 138 performed well for the shock tube measurements but not satisfactorily for RCM conditions, it is worth finding out the difference between the key reactions for these two conditions. The sensitivity analyses for Jiang-2019 and Li-2019 are compared in the left panel of Figure 18 for the shock tube conditions.…”
Section: Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of utilizing ammonia in combustion equipment, pertinent studies have tested and applied ammonia in internal combustion engines, 10‐12 gas turbines, 13‐15 etc. Meanwhile, in order to support the application and have better understanding of ammonia combustion, fundamental studies also have been performed using ammonia fuels 16‐19 . Generally, the ammonia combustion studies have proved the feasibility for potential combustion applications.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in order to support the application and have better understanding of ammonia combustion, fundamental studies also have been performed using ammonia fuels. [16][17][18][19] Generally, the ammonia combustion studies have proved the feasibility for potential combustion applications. Although previous work has made a good progress in the utilization and understanding of ammonia combustion, there are still lots of issues which need to be better settled.…”
Section: Introductionmentioning
confidence: 99%